Editorial – 7th World Engineering Conference on Contemporary Technologies™ (WECON™ 2022). (2022) - Juneja, Sagar; Pandey, Rahul; Madan, Jaya; Mantri, Archana; Gupta, R.S.; Sharma, Rajnish
Abstract: Launched in 2008, World Engineering Conference on Contemporary Technologies™ (WECON™) is a flagship engineering conference of Chitkara University, Punjab, India. The 7th edition of the conference (WECON 2022) has been organized during May 20–21, 2022 in collaboration with Elsevier as publication partner and attended by 200 delegates in a virtual mode. Conference featured 50 paper presentations in 5 parallel tracks, 4 keynote talks, and 9 invited talks. In this editorial, an overview of the theme of WECON 2022 and technical program details of the conference are presented. Additionally, a brief history of the conference, and efforts of Chitkara University in organizing and supporting WECON for the last 14 years are also discussed. Finally, the editorial acknowledges all the committees and entities that have contributed toward the success of the conference.